2021
DOI: 10.1136/bmjgh-2021-005757
|View full text |Cite
|
Sign up to set email alerts
|

Parental and professional perceptions of informed consent and participation in a time-critical neonatal trial: a mixed-methods study in India, Sri Lanka and Bangladesh

Abstract: IntroductionTime-critical neonatal trials in low-and-middle-income countries (LMICs) raise several ethical issues. Using a qualitative-dominant mixed-methods design, we explored informed consent process in Hypothermia for encephalopathy in low and middle-income countries (HELIX) trial conducted in India, Sri Lanka and Bangladesh.MethodsTerm infants with neonatal encephalopathy, aged less than 6 hours, were randomly allocated to cooling therapy or usual care, following informed parental consent. The consenting … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The supportive care for neonatal units that do not have basic neonatal care as in sub-Saharan Africa [ 50 ] would be very different to the situation in south Asian neonatal units with good neonatal intensive facilities, and no generalizations should be made. If a hospital has no facility for basic neonatal care, it would be prudent to establish this first before introducing novel neuroprotective interventions [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The supportive care for neonatal units that do not have basic neonatal care as in sub-Saharan Africa [ 50 ] would be very different to the situation in south Asian neonatal units with good neonatal intensive facilities, and no generalizations should be made. If a hospital has no facility for basic neonatal care, it would be prudent to establish this first before introducing novel neuroprotective interventions [ 51 ].…”
Section: Introductionmentioning
confidence: 99%
“…Consistently high scores were obtained under these domains indicating adequate quality of informed consent, i.e., appropriate information was provided to parents. Subsequently, qualitative interviews with parents and professional were conducted to explore their views about the research participation [ 51 ]. Thematic analysis of the data suggested that the parental decision to participate was primarily based on an unreserved trust in the treating doctors, therapeutic misconception, and the opportunity to have an expensive treatment free of cost.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Neonatal clinical trials in low and middle-income countries (LMICs) recruiting underprivileged population are challenging and require different approaches to high-income countries. In particular, parental consent rates of almost 100% in neonatal drug trials in LMICs raise concerns about the quality of informed consent 10 11. The high consent rates may be related to a wide range of factors including a genuine trust in treating clinicians,11 therapeutic misconception,11 lucrative financial incentives, especially in pharmaceutical trials managed by contract research organisations,12 13 or even complete unawareness about trial participation 14.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, parental consent rates of almost 100% in neonatal drug trials in LMICs raise concerns about the quality of informed consent 10 11. The high consent rates may be related to a wide range of factors including a genuine trust in treating clinicians,11 therapeutic misconception,11 lucrative financial incentives, especially in pharmaceutical trials managed by contract research organisations,12 13 or even complete unawareness about trial participation 14. Hence, careful monitoring and transparent reporting of these issues are important to enhance the credibility of clinical trials in LMICs.…”
Section: Introductionmentioning
confidence: 99%